The effects of on-farm produced feeds on growth, survival, yield and feed cost of juvenile African sharptooth catfish (Clarias gariepinus) - Limbu, Samwel Mchele (Aquaculture and fisheries, 2020)
The culture of African sharptooth catfish (Clarias gariepinus) in most developing countries lacks suitable diets for semi-intensive production. The present study evaluated the growth performance, survival, nutrient utilization, hepatosomatic index (HSI), body composition, yield and feeding cost of African catfish fed on semi-intensive feeds 1 (SMF1) and semi-intensive feed 2 (SMF2) produced on-farm and an industrially manufactured (IM) feed as a control. Two hundred fish (14.95 ± 0.24 g) were stocked in triplicate earthen ponds and fed the three diets at 5% of the body weight for eight weeks. The final weight, specific growth rate and yield of fish fed the SMF2 diet was significantly lower than SMF1 and IM diets. However, no significant differences were revelead in final weight, specific growth rate and yield between fish fed SMF1 and IM diets. The survival rate, feed conversion ratio and protein efficiency ratio of fish did not differ among the diets. Apparent net protein utilization was significantly higher on fish fed the SMF2 and SMF1 diets than IM diet. The HSI of fish fed the IM diet was significantly higher and the livers were yellow-coloured compared to smaller and brownish/reddish livers of fish fed the SMF1 and SMF2 diets. The fish fed the IM diet had statistically lower ash content than SMF1 diet. The incidence cost of fish fed the IM diet was 35% higher, while its profit index was 31% lower than fish fed the SMF1 and SMF2 diets. Taken together, African catfish farmers can reduce feed cost up to 30% by using on-farm produced feeds when formulated properly and blended without affecting fish growth performance, survival and yield while obtaining better protein retention and healthier fish.